2011
DOI: 10.1016/j.reseneeco.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for electric vehicles and their attributes

Abstract: This paper presents a stated preference study of electric vehicle choice using data from a national survey. We used a choice experiment wherein 3029 respondents were asked to chose between their preferred gasoline vehicle and two electric versions of that preferred vehicle. We estimated a latent class random utility model and used the results to estimate the willingness to pay for five electric vehicle attributes: driving range, charging time, fuel cost saving, pollution reduction, and performance. Driving ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
401
11
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 855 publications
(499 citation statements)
references
References 18 publications
32
401
11
5
Order By: Relevance
“…A similar result is observed by Krause et al (2016), whose assessment of vehicle preferences in the USA found that 44% of consumers would select a pure battery EV under the conditions of price and performance parities. The high costs associated with the production of EV battery packs are often cited as the primary source of EV price premiums and thus one of the main inhibitors of adoption (Axsen et al 2010;Hidrue et al 2011).…”
Section: Past Researchmentioning
confidence: 99%
“…A similar result is observed by Krause et al (2016), whose assessment of vehicle preferences in the USA found that 44% of consumers would select a pure battery EV under the conditions of price and performance parities. The high costs associated with the production of EV battery packs are often cited as the primary source of EV price premiums and thus one of the main inhibitors of adoption (Axsen et al 2010;Hidrue et al 2011).…”
Section: Past Researchmentioning
confidence: 99%
“…Perhaps the average 13 consumer is willing to stop for longer if this implies that they would have to stop less often. The 14 difference in additional willingness-to-pay (WTP) for reducing charging time from 1 hour to ten minutes 15 is roughly similar to the additional WTP for increasing the performance of the electric vehicle from 5% 16 slower than a gasoline vehicle to 5% faster (Hidrue et al, 2011). 17…”
Section: Why Didn't Better Place Overcome Range Anxiety? 13mentioning
confidence: 85%
“…According to Santini and Vyas (2005), Potoglou and Kanaroglou (2007), and Hidrue at al. (2011), younger people with higher education and those who are more interested in new technology are inclined to prefer electric cars.…”
Section: Forecasting Market Shares Of Environment-friendly Vehicles Umentioning
confidence: 99%